Importance of Machine Learning Techniques to Improve the Open Source Intrusion Detection Systems - Fatimetou Abdou VADHIL; Mohamedade Farouk NANNE; Mohamed Lemine SALIHI (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Nowadays, it became difficult to ensure data security because of the rapid development of information technology according to the Vs of Big Data. To secure a network against malicious activities and to ensure data protection, an intrusion detection system played a very important role. The main objective was to obtain a high-performance solution capable of detecting different types of attacks around the system. The main aim of this paper is to study the lacks of traditional and open source Intrusion Detection Systems and the Machine Learning techniques commonly used to overcome these lacks. A comparison of some existing works by Intrusion Detection System type, detection method, algorithm and accuracy was provided.